1978
DOI: 10.1172/jci109010
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation and secretion of platelet Factor 4 during blood clotting.

Abstract: A B S T R A C T We have studied the platelet release reaction and thrombin generation during the spontaneous clotting of whole blood in vitro. Both thrombin formation and secretion of platelet Factor 4 were detected at least 12 min before clotting (clotting time, 22-26 min). Initially, at low thrombin concentrations (2-5 ng/ml), there is a small increase in plasma platelet Factor 4 (<1% of the amount present in serum). This is followed by a gradual increase in both platelet Factor 4 and thrombin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 21 publications
(22 reference statements)
3
23
0
Order By: Relevance
“…Prior investigators have measured either the appearance of a thrombin-related neoantigen or the cleavage of fibrinopeptide A by thrombin (10,12,13,15 antithrombin complexes form in plasma, albeit somewhat more slowly than the prediction derived from experiments with the purified proteins (21). The fact that platelets undergo release when only 3-5 nM F1+2 has been cleaved suggests that some thrombin is being formed, since platelets neither bind nor react to any of the prothrombin intermediates (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior investigators have measured either the appearance of a thrombin-related neoantigen or the cleavage of fibrinopeptide A by thrombin (10,12,13,15 antithrombin complexes form in plasma, albeit somewhat more slowly than the prediction derived from experiments with the purified proteins (21). The fact that platelets undergo release when only 3-5 nM F1+2 has been cleaved suggests that some thrombin is being formed, since platelets neither bind nor react to any of the prothrombin intermediates (22).…”
Section: Discussionmentioning
confidence: 99%
“…Shuman and Levine (13) used such radioimmunoassay techniques to study the generation of thrombin during coagulation of native whole blood and were able to closely relate thrombin generation and platelet secretion. They concluded that platelet secretion required thrombin, but that inhibition of platelet release did not influence the rate of thrombin generation (13,14). Kaplan and co-workers (10), who added thrombin to washed platelet suspensions containing fibrinogen, or to citrated plasma, noted that the release of fibrinopeptide A, a thrombin-specific cleavage product, preceded platelet release of 8-thromboglobulin or platelet factor 4 (PF-4) and suggested that fibrinogen was the preferred substrate for exogenous thrombin.…”
mentioning
confidence: 99%
“…Because it stimulates platelet secretion at concentrations that are generated physiologically (1-2 nM), it is likely to be important in the initiation ofthe platelet thrombus formed in response to vascular injury (2,3). The mechanism by which thrombin stimulates platelet secretion is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin converts fibrinogen into fibrin which forms part of the blood clot, 1,2) and activates other blood coagulation factors such as V, VIII, XIII, and protein C.3) Moreover, thrombin also activates blood platelets, 4,5) and acts as a mitogen for various cell types. [6][7][8] Thus, thrombin has become a special target in the design and development of antithrombotic agents.…”
mentioning
confidence: 99%
“…3) Moreover, thrombin also activates blood platelets, 4,5) and acts as a mitogen for various cell types. [6][7][8] Thus, thrombin has become a special target in the design and development of antithrombotic agents.…”
mentioning
confidence: 99%